(untitled) (Research, Society and Development, 2020)
Introduction: Kidney transplant (KT) has the highest survival rate amongst kidney replacement therapies (KRT). Objective: Analyze the incidence density of all-cause mortality in chronic kidney disease transplant-recipients and to identify covariables associated with higher risk of death. Methodology: Cohort study using medical records of 605 KT patients with seven years follow-up (2011-2018). Records with insufficient data or from patients with incomplete treatment were excluded. The variables analyzed were demographic, clinical and laboratory data, duration of KRT, type of donor, immunological compatibility, panel-reactive HLA-antibody, infections, and use of hypothermic perfusion machine (HPPM). Hazard ratio (HR) and incidence density of all-cause deaths were estimated. Results: 15 of 553 KT-recipients died during the follow-up. The survival in the first year post-KT was 98.0% and in the fifth year was 93.2%. The incidence density of deaths is 10/1,000 person-years. Variables pre- and post-KT related with higher death risk were allograft pyelonephritis ≥6-months and delayed graft function >4 weeks. Survival among KT-recipients with loss >5 mL/min/1.73m2/year in the estimated glomerular filtration rate (eGFR) were lower than the others (88% vs. 97%). Covariates associated with mortality post-transplant included pre-KT obesity, HPPM, allograft pyelonephritis, and new-onset diabetes after transplantation. Conclusion: The mortality post-KT is low in these population. Cox’s modelling demonstrated that the decline in eGFR >5 mL/min/1.73m2/year, allograft pyelonephritis ≥6-months, pre-KT obesity, fasting blood glucose ≥126 mg/dL presented worst probability of survival. Rapid decline in eGFR reduces substantially the survival probability in these population.